Enhancing the Competitiveness of Traditional Tempe Chip SMEs: A Marketing Strategy Analysis of Dua Karunia in Sanan Village, Malang - Evi Suwarni; Sudarmiatin Sudarmiatin; Agus Hermawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The tempe chip industry in Sanan Village, Malang City, represents a culturally embedded small and medium enterprise (SME) cluster that has contributed to the local economy for decades. However, intensifying intra-cluster competition, soybean price volatility, and shifting consumer behavior have placed increasing pressure on the competitiveness of businesses in this area. This study aims to analyze the marketing strategy implemented by Keripik Tempe Dua Karunia — one of the pioneering enterprises in Sanan Village that has been operating since 1980 — and to identify the marketing strategy factors that contribute to enhancing its competitive advantage. A qualitative descriptive approach was employed through field observation, in-depth interviews with the business owner, and documentation analysis. The analysis is grounded in the 4P marketing mix framework — Product, Price, Place, and Promotion. The findings reveal that Dua Karunia builds its competitiveness through four strategic pillars: (1) product differentiation through multi-flavor diversification and consumer-driven customization; (2) cost-based pricing that is adaptively managed through shrinkflation tactics in response to raw material price fluctuations; (3) multi-channel distribution that integrates direct outlet sales with digital platforms (Shopee and WhatsApp); and (4) long-established word-of-mouth reputation-based promotion reinforced by active e-commerce presence. This study concludes that the consistent integration of all four marketing mix elements, supported by family-based operational flexibility and the cultural heritage value embedded in the product, constitutes the primary source of sustained competitive advantage for Dua Karunia amid increasingly intense cluster competition. These findings carry practical implications for similar SMEs seeking to design adaptive, competitiveness-oriented marketing strategies.